Optimization of milling carbon fibre reinforced plastic under chilled air machining - Muhamad Khairussaleh, Nor Khairusshima; Syed Shaharuddin, Sharifah Imihezri (Elsevier Ltd, 2017)
Carbon fibre reinforced plastic (CFRP) is an expensive composite that, as industry demand for this composite has increased, has become a valuable material. CFRP is suitable to be used in automotive, aerospace and aircraft industries, because of its properties, which are being stronger than steel and stiffer than titanium, while retaining its lighter weight. This paper presents the optimization of cutting parameters during milling CFRP under chilled air machining. A Central Composite Design (CCD) of the Response Surface Method (RSM) has been used to design the experimental runs and to develop a mathematical model based on the data collected. The experiments were arranged using various cutting parameters of cutting speed (160- 200 m/min), feed rate (0.125-0.375 mm/tooth), and depth of cut (0.5-1.0 mm). In this study, air pressure of 0.55 MPa and chilled air (with a temperature of -10 degrees and a flow velocity of 4.10 m/s) were applied to the cutting tool using a vortex tube. It have been observed that the optimized cutting parameters were cutting speed, feed and depth of cut of 194 m/min, 0.5 mm/tooth and 0.5 mm, respectively, with tool life, surface roughness and delamination factor at 9.287 minutes, 1.585 μm and 1.086, respectively.